الثقافة الذاتية وأثرها في التعبير الفني عن الحب دراسة تحليلية مقارنة في أدب جبران خليل جبران وشيو جي مؤه - يحيى، إسحاق (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2015)
This study aims to investigate the literary lives of the Arab poet Gibran Khalil Gibran and the Chinese poet Xu Zhimo to identify the roots of charm of their poetry and their artistic expressions on love. The study tries to answer the following important questions: What are the general characteristics of free poem in both the Arabic and the Chinese worlds? What are the similarities and differences between their experiences and their ways in artistic expression? What are factors those inlfuenced the literary character of both? Accordingly, the researcher started by introducing the two roots of poets Gibran Khalil Gibran and Xu Zhimo and analyzing the factors that affected their compositions. The research also analyzes the poems in wich both of the expression of their expperiences and indicated the artistic creativity of each and the impact of their culture background on their poems. Finally, it reveals the similarities and differences between their experiences either in the artistic expression or the content. The study recommends carrying out more comparative studies between Arabic and Chinese literature because a lot of precious literary works are still in need to be studied and even translated from one language to the other.